Postoperative blood transfusion is an independent predictor of acute kidney injury in cardiac surgery patients - Kristofer Freeland; Alireza Hamidian Jahromi; Lucas Maier Duvall; Mary Catherine Mancini (Society of Diabetic Nephropathy Prevention, 2015)
Background: Acute kidney injury (AKI) is a serious complication of cardiac surgery with cardiopulmonary bypass (CPB) which increases postoperative morbidity and mortality. Objectives: The study was designed to assess the incidence of AKI and associated risk factors in patients undergoing CPB ancillary to coronary artery bypass grafting (CABG), valve surgery, and combined CABG and valve surgery. Patients and Methods: This Intuitional Review Board (IRB) approved retrospective study included patients with normal preoperative kidney function (Serum creatinine [sCr] <2.0 mg/dl) who underwent cardiac surgery with CPB between 2012 and 2014. Patients were divided into 2 groups: group I: Patients with cardiac surgery associated AKI (CS-AKI) (postoperative sCr >2 mg/dl with a minimal doubling of baseline sCr) and group II: Patients with a normal postoperative kidney function. Demographic data, body mass index (BMI), co-morbidities, hematologic/biochemical profiles, preoperative ejection fraction (%EF), blood transfusion history, and operative data were compared between the groups. Mean arterial pressure (MAP) was recorded during the operation and in the postoperative period. Δ-MAP was defined as the difference between pre-CPB-MAP and the CPB-MAP. Results: 241 patients matched the inclusion criteria (CS-AKI incidence = 8.29%). Age, gender, BMI, %EF, and co-morbidities were not predictors of CS-AKI (P > 0.05). High preoperative sCr (P = 0.047), type of procedure (P = 0.04), clamp time (P = 0.003), pump time (P = 0.005) and history of blood transfusion within 14 days postsurgery (P = 0.0004) were associated with risk of CS-AKI. Pre-CPB-MAP, CPB-MAP, Δ-MAP, and ICU-MAP were not significantly different between the 2 groups. Male gender (OR: 5.53; P = 0.048), age>60 (OR: 4.54; P = 0.027) and blood transfusion after surgery (OR: 5.25; P = 0.0054) were independent predictors for postoperative AKI. Conclusions: Age, gender and blood transfusion were independent predictors of cardiac surgery associated AKI.